2010
DOI: 10.1111/j.1525-139x.2009.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining a Hemodialysis Exercise Program: A Review

Abstract: This article reviews the literature addressing exercise programs for dialysis patients to identify elements necessary for sustaining exercise programs in this population. Literature searches for publications (January 1980-February 2009) in Medline (OVID), PubMed, CINAHL (EBSCO), EBSCOhost EJS, ProQuest Central, Web of Science, Cochrane Library, Google Scholar, ScienceDirect, SpringerLink (Kluwer), and Wiley Interscience (Blackwell) were performed. Reference lists from relevant articles were hand-searched for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 116 publications
(231 reference statements)
2
78
0
6
Order By: Relevance
“…Social support is a multidimensional concept that includes emotional (communication of empathy and esteem) and instrumental support (offering assistance and information) (27). Previous publications have emphasized the technical role of the exercise specialist in IDE (25,26), consistent with instrumental support. However, it was the emotional interpretation of this technical support that seemed critical to enhancing perceptions of the intervention's effectiveness and facilitated high acceptability of IDE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support is a multidimensional concept that includes emotional (communication of empathy and esteem) and instrumental support (offering assistance and information) (27). Previous publications have emphasized the technical role of the exercise specialist in IDE (25,26), consistent with instrumental support. However, it was the emotional interpretation of this technical support that seemed critical to enhancing perceptions of the intervention's effectiveness and facilitated high acceptability of IDE.…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of exercise professional support in sustaining an IDE program has been recognized (25,26), how support functions to enhance the effectiveness of IDE and what may be required from those delivering IDE are unknown. We identified the support of the kinesiologist as a key component of IDE implementation.…”
Section: Discussionmentioning
confidence: 99%
“…The staff can be incorporated into the exercise intervention program with MHD patients, to develop a truly individualized physical activity program. 54 In the present study, laboratory parameters were explored as predictors of fatigue. We found that fatigue was negatively correlated with Scr concentrations and positively correlated with Kt/V level rather than with other laboratory variables.…”
mentioning
confidence: 99%
“…Despite the significant impact of exercise on hemodialysis patients, these patients are inactive and have reduced physical activity and function (18,19). Unawareness of the benefits of exercise, fear of injury, experience of disability, low power to exercise, lack of motivation, lack of sports facilities and lack of financial support are some of the reasons which decrease levels of mobility and exercise in hemodialysis patients (20)(21)(22)(23). Various problems caused by physical inactivity have some effects on various aspects of lives of patients undergoing hemodialysis.…”
Section: Introductionmentioning
confidence: 99%